Automation Based Library Management in Depok Public Library In The Context of Ritual Performance - Maulidia, Rafiqa; Laksmi, Laksmi (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2017)
Library management using manual system is no longer adequate to handle the workload in the library routines, librarians must use application of library automation. To provide a good working performance, librarians use strategy, competences and certain habits, which are referred to as a ritual performance. The performance of the ritual is the demonstration of competence spontaneously by individuals in dealing with individuals, groups and organizations, which contains elements of personal ritual, the work ritual, social ritual, and organization ritual. The research focuses in the automation based library management in the context of the performance of the ritual. This study used a qualitative approach with case study method. The findings suggest that the personal ritual shows the personal habits of librarians to do their tasks, ritual librarians work show responsibility towards their duties, social rituals strengthen the emotional connection between librarians and leaders, as well as ritual organizations suggest the involvement of librarians in giving their contribution in decision making. Conclusions of this study shows that the performance of rituals librarian at Depok Public Library gives librarians the skills to implement automation systems in the library management, and reflect the values of responsibility, mutual trust, and mutual respect.